1998
DOI: 10.1002/(sici)1521-3765(19980416)4:4<672::aid-chem672>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific and Kinetic Control over the Hydrolysis of a Sterically Hindered Platinum Picoline Anticancer Complex

Abstract: cis-[PtCl 2 (NH 3 )(2-picoline)] (1) (AMD 473) is a recently reported active anticancer complex. Hydrolysis may be an important step in its intracellular activation and interaction with DNA. In this paper we employed [ 1 H, 15 N] 2 D NMR spectroscopy to determine the hydrolysis rates for each chloride ligand of this complex and its 3-picoline analogue 2. We also report the pK a values of the aqua and diaqua ligands as well as the X-ray crystal structures of 1 and 2. For the 3-picoline complex 2 the rate of hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
110
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 14 publications
12
110
0
2
Order By: Relevance
“…This principle has been adopted for the related platinum anticancer complex cis-[Pt(NH 3 )(2-picoline)Cl 2 ] (picoplatin), which is currently undergoing clinical trials (11). The reactions of picoplatin with water and other nucleophiles are much slower than those of cisplatin and related complexes lacking steric hindrance at the axial sites (12)(13)(14). The lesser reactivity of picoplatin, particularly with thiols, prevents undesired deactivation of the complex before it can reach DNA.…”
Section: Resultsmentioning
confidence: 98%
“…This principle has been adopted for the related platinum anticancer complex cis-[Pt(NH 3 )(2-picoline)Cl 2 ] (picoplatin), which is currently undergoing clinical trials (11). The reactions of picoplatin with water and other nucleophiles are much slower than those of cisplatin and related complexes lacking steric hindrance at the axial sites (12)(13)(14). The lesser reactivity of picoplatin, particularly with thiols, prevents undesired deactivation of the complex before it can reach DNA.…”
Section: Resultsmentioning
confidence: 98%
“…These structural features are similar to those of the 2-picoline complex AMD473 (103°and H 3 C···Pt 3.22 Å ). [4] The PtϪN1 distance (2.028 Å ) is also similar to that of the 2-picoline complex (2.017 Å ). No intramolecular hydrogen bonding is observed between the hydroxyl group and the two Cl ligands.…”
Section: Resultsmentioning
confidence: 99%
“…[2,3] In reactions of cisplatin with DNA, hydrolysis is known to be the rate-limiting step. The steric influence of 2-picoline plays an important role in decreasing the rates of hydrolysis and substitution reactions of AMD473, [4,5] and also in promoting high stereoselectivity in the formation of a GG intrastrand adduct with a 14-mer DNA duplex. [6] In order to elucidate further the role of pyridine substituents in determining the reactivity of platinum(II) picoline complexes, we have studied the hydrolysis rates of the AMD473 analogue cis-[PtCl 2 (NH 3 ){2-(2-hydroxyethyl)pyridine}] (1) and determined the pK a values of its monoaqua and diaqua adducts by [ 1 H, 15 N] NMR studies of complex 1 labelled with 15 NH 3 .…”
Section: Introductionmentioning
confidence: 99%
“…204 This provides steric hindrance to the attack of the drug by nucleophiles, particularly thiols. In vitro studies demonstrated picoplatin's ability to overcome platinum drug resistance, showing anticancer activity in cisplatin, carboplatin and oxaliplatin resistant cell lines.…”
Section: -203mentioning
confidence: 99%